Fish faces - Wu, Norbert (New York : Holt, 1997)
The author-photographer, a marine biologist, uses his own photographs to introduce readers to some of the more amusing characteristics of the creatures he's encountered on his dives.
Elem. School Library Collection
Publisher's Weekly
School Library Journal
1.7
K-3
K-3
Keywords: Fishes -- Juvenile literature; Fishes; Marine biology; Fishes; Marine biology